The Implementation of Guidance of Akhlakul Karimah in Islamic Education Subject at SMP Negeri 2 Bangun Purba Deli Serdang - Wahyudin Nur Nasution; Siti Halimah; Ridwan Harahap; M. Fajri Syahroni Siregar (IAIN Padangsidimpuan, 2021)
This study is to describe the implementation of moral development in Islamic religious education subjects at SMP Negeri 2 Bangun Purba, Deli Serdang Regency. The implementation includes implementation, obstacles and strategies. This type of research is a qualitative research with a descriptive approach, namely research that seeks to describe events in the field as they are. This study used various techniques such as interviews, observation, and documentation in collecting the data. The primary data sources in this study were school principals, Islamic Religious Education (PAI) teachers, and Counseling Guidance (BK) teachers. While the data analysis using the Miles and Huberman model which includes data reduction, data presentation, to drawing conclusions. The results of the study concluded that the activities carried out in implementing moral development were praying before and after teaching and learning activities, reading the Qur'an for 10 minutes before learning began, and performing the midday prayer in congregation. Meanwhile, the obstacles faced by teachers in fostering morality are factors from the students themselves, the lack of parental roles in children's education, school supervision that has not been maximized, and the Muslim minority environment. The efforts made by the teacher in fostering moral character are by exemplary methods, habituation, motivation, and advice.